Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I want to prove basic results of Cyclotomic polynomial over $\mathbb{Q}$

$(1) \Phi_n(0)=1$ for all $n>1$

$(2) \Phi_{2n}(x)=\Phi_n(-x)$ for all odd number $n>1$

I want use this result as definition: For every positive integer $n$,

$$ x^{n}-1=\prod_{d|n} \Phi_{d}(x)$$

where $d$ runs over all positive divisors of $n$.

share|improve this question

3 Answers 3

up vote 2 down vote accepted

The OP does not say what additional information may be used, so here are two answers that use Möbius inversion as in $$\Phi_n(x) = \prod_{d|n} (x^d-1)^{\mu(n/d)}$$ since this is a instant consequence of the formula you were given to work with.

Using this formula we have immediately that $$\Phi_n(0) = \prod_{d|n} (-1)^{\mu(n/d)} = (-1)^{\sum_{d|n} \mu(n/d)}.$$ Now for $n>1$ we have $\sum_{d|n} \mu(n/d) = 0$, and hence $\Phi_n(0) = (-1)^0 = 1.$ For $n=1$ we get $\Phi_1(0) = (-1)^1 = -1.$ For the second part start with $$\Phi_n(-x) = \prod_{d|n} ((-x)^d-1)^{\mu(n/d)}.$$ Now since $d$ is odd we have $(-x)^d = (-1)^d x^d = -x^d$, giving $$ \prod_{d|n} (-x^d-1)^{\mu(n/d)} = \prod_{d|n} \left(\frac{x^{2d}-1}{-x^d+1}\right)^{\mu(n/d)} = \prod_{d|n} (-1)^{\mu(n/d)} \prod_{d|n} \left(\frac{x^{2d}-1}{x^d-1}\right)^{\mu(n/d)}\\ = \prod_{d|n} (-1)^{\mu(n/d)} \prod_{d|n} \left(\frac{x^d-1}{x^{2d}-1}\right)^{\mu(2n/d)} \\= \prod_{d|n} (-1)^{\mu(n/d)} \prod_{d|n} \left(\frac{x^d-1}{x^{2d}-1}\right)^{\mu(2n/d)} \prod_{d|n} \left(\frac{x^{2d}-1}{x^{2d}-1}\right)^{\mu(2n/d/2)}\\ = \Phi_{2n}(x) \prod_{d|n} (-1)^{\mu(n/d)} \prod_{d|n} \frac{1}{(x^{2d}-1)^{\mu(2n/d)}(x^{2d}-1)^{\mu(n/d)}}\\ = \Phi_{2n}(x) \prod_{d|n} (-1)^{\mu(n/d)} \prod_{d|n} \frac{1}{(x^{2d}-1)^{\mu(2n/d)+\mu(n/d)}}.$$ Now since $n>1$ we have $\prod_{d|n} (-1)^{\mu(n/d)}=1$ and $\mu(2n/d)+\mu(n/d)=0$ so that the final answer is $$ \Phi_{2n}(x) \times 1 \times \prod_{d|n} \frac{1}{(x^{2d}-1)^0} = \Phi_{2n}(x).$$

share|improve this answer
    
In the 2nd proof how to get 3rd setp?(in the power you changed $\mu(2n/d)$) –  Siddhant Trivedi Nov 2 '13 at 6:32
    
What a proof!really great. –  Siddhant Trivedi Nov 2 '13 at 7:33
    
Can u give me any proof of first formula? or any link for this. –  Siddhant Trivedi Nov 2 '13 at 7:36

1. Remark that $n=1$ is an exception, since $\Phi_1(0) = -1$. Since $x^n-1 = \prod_{d \mid n} \Phi_d(x)$, putting $x=0$ on both sides yields $$-1 = \prod_{d\mid n} \Phi_d(0).$$ Now use induction on $n$, and the fact that $\Phi_1(0)$ accounts for a factor of $-1$ on the right-hand side.


2. Remark that $n=1$ is again an exception, because $\Phi_2(x) = x+1 = -\Phi_1(-x)$. Now, for a general odd $n$,

$$\prod_{d \mid 2n} \Phi_d(x) =x^{2n}-1 = (x^n-1)(x^n+1) = -(x^n-1)((-x)^n-1) = -\prod_{d \mid n} \Phi_d(x)\Phi_d(-x).$$

Now we use induction on $n$. The divisors of $2n$ come in pairs $(d, 2d)$, where $d$ is a divisor of $n$. By the induction hypothesis, $\Phi_{2d}(x) = \Phi_d(-x)$ for each proper divisor of $n$, except when $n=1$ when there is an extra minus sign. By comparing both sides it follows that $\Phi_{2n}(x) = \Phi_n(-x)$.

share|improve this answer
    
in the right hand side(last term) how can i get $\Phi_{n}(-x)$?i had done induction but i get two times product on divisors. –  Siddhant Trivedi Nov 2 '13 at 5:22
    
@SiddhantTrivedi The right-hand side can be written as $-\Phi_n(x)\Phi_n(-x) \prod_d \Phi_n(d)\Phi_n(-d)$ where the product is over the proper divisors of $n$. The left-hand side can be written as $\Phi_n(x)\Phi_{2n}(x) \prod_d \Phi_d(x)\Phi_{2d}(x)$, where the product is also over the proper divisors of $n$. Now apply induction... –  Bruno Joyal Nov 2 '13 at 5:31
    
very nice, thanks Bruno! –  1LiterTears Feb 2 at 19:41
    
My pleasure, @1LiterTears ! –  Bruno Joyal Feb 3 at 1:44

Here is another answer that uses the basic definition $$\Phi_n(x) = \prod_{1\le k\le n \atop \gcd(k,n)=1} (x-e^{2\pi i k/n}).$$ This gives $$\Phi_n(0) = (-1)^{\varphi(n)} \prod_{1\le k\le n \atop \gcd(k,n)=1} e^{2\pi i k/n}.$$ Now recall that for $n>1$ we have $$\sum_{1\le k\le n \atop \gcd(k,n)=1} k = \frac{1}{2} \varphi(n) n.$$ This gives $$\Phi_n(0) = (-1)^{\varphi(n)} e^{(2\pi i/n) \times 1/2\times \varphi(n) \times n} = (-1)^{\varphi(n)} e^{\pi i \varphi(n)} = (-1)^{2\varphi(n)} =1.$$

For the second part we get that $$\Phi_n(-x) = \prod_{1\le k\le n \atop \gcd(k,n)=1} (-x-e^{2\pi i k/n}) = (-1)^{\varphi(n)} \prod_{1\le k\le n \atop \gcd(k,n)=1} (x+e^{2\pi i k/n}) \\ = (-1)^{\varphi(n)} \prod_{1\le k\le n \atop \gcd(k,n)=1} (x-e^{\pi i + 2\pi i k/n})= (-1)^{\varphi(n)} \prod_{1\le k\le n \atop \gcd(k,n)=1} (x-e^{2\pi i (k/n+1/2)})\\ = (-1)^{\varphi(n)} \prod_{1\le k\le n \atop \gcd(k,n)=1} (x-e^{2\pi i (2k+n)/(2n)}).$$ This almost concludes the proof. We can ignore the sign because $\varphi(n)$ is even.

We now claim there is a bijection between the primitive roots modulo $2n$ call them of class $\mathcal{P}_1$ given by $e^{2\pi i k/(2n)}$ where $\gcd(k,2n)=1$ and $1\le k\le 2n$ and the values produced by $e^{2\pi i (2k+n)/(2n)}$ call them of class $\mathcal{P}_2$ where $\gcd(k,n)=1$ and $1\le k\le n.$ (These two conditions will be our domain of $k.$)

Let $\mathcal{Q}$ be the class of primitive roots modulo $n$. The $\mathcal{P}_1$ roots can be obtained from these by taking $q$ as is if it is odd and taking $q+n$ if it is even (recall that $n$ is odd). Now to establish a bijection to $\mathcal{P}_2$ we must show that $q\equiv 2k+n\bmod (2n)$ and $q+n\equiv 2k+n\bmod (2n)$ always have a unique solution $k$ in the domain of $k$. In the first case we take $k=(q+n)/2$ which is easily seen to be in this domain. In the second case take $k=q/2,$ also clearly in this domain. Moreover we clearly hit each value of $k$ exactly once. This finishes the proof.

share|improve this answer
    
for $n>1$ how can i prove this? $$\sum_{1\le k\le n \atop \gcd(k,n)=1} k = \frac{1}{2} \varphi(n) n.$$ –  Siddhant Trivedi Nov 2 '13 at 5:29
    
I got it.Thanks. –  Siddhant Trivedi Nov 2 '13 at 6:19

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.